Preparation method of mulberry bark regenerated cellulose fiber

The combination of dialdehyde cellulose in the composite modifier with regenerated cellulose fibers and polyurethane prepolymers is formed, which solves the problem of degradation in the performance of traditional regenerated cellulose fibers in high humidity environments and significantly improves the Wet strength and wear resistance.

CN119287544AInactive Publication Date: 2025-01-10YANCHENG JINLAN TEXTILE RAW MATERIALS CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411634490.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional regenerated cellulose fibers have deteriorated mechanical properties in high humidity environments, are prone to fracture or deformation, and have poor wear resistance, so they cannot maintain excellent performance under humid conditions.

Method used

Using a composite modifier, a covalent bond is formed by cross-linking dialdehyde cellulose with regenerated cellulose fibers, and a flexible chain segment of the polyurethane prepolymer is combined to form a three-dimensional network structure to improve the wet strength and wear resistance of the fibers.

Benefits of technology

It improves the strength, elasticity and wear resistance of regenerated cellulose fibers in wet state, ensuring good mechanical properties and dimensional stability in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FKOUGKUDB3YENP2US9FG7SOAMY3NKPYTHLUCWOFX
    Figure FKOUGKUDB3YENP2US9FG7SOAMY3NKPYTHLUCWOFX
Patent Text Reader

Abstract

The invention relates to the technical field of regenerated cellulose fibers, in particular to a preparation method of mulberry bark regenerated cellulose fibers, the fineness of the mulberry bark regenerated cellulose fibers is 1.11 dtex-2. 22 dtex, the length is 32-51 mm, and the diameter of the mulberry bark regenerated cellulose fibers is 10-20 micrometers. S1.1, weighing the following raw materials in parts by weight: 1-5 parts of a composite modifier, 45-55 parts of mulberry bark, 12-22 parts of sodium hydroxide, 0.4-0.6 part of sodium hypochlorite, 5-7 parts of carbon disulfide and 200-220 parts of coagulating bath; the coagulating bath consists of sulfuric acid, sodium sulfate and zinc sulfate; s1.1, preparing pulp from mulberry bark; s1.2, mulberry bark regenerated cellulose fibers are prepared from pulp, a composite modifier is adopted, and the wet strength, the size stability and the shrinkage rate performance of the regenerated cellulose fibers are improved through the synergistic effect of the mulberry bark regenerated cellulose fibers, the pulp and the composite modifier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of regenerated cellulose fibers, in particular to a method for preparing mulberry bark regenerated cellulose fibers. Background Art

[0002] As a high-performance and environmentally friendly fiber material, regenerated cellulose fiber has been widely used and praised in many fields such as textiles, clothing and home textiles in recent years. It uses natural cellulose (such as cotton, linen, bamboo, trees, etc.) as raw materials and is processed through advanced chemical processes. It does not change its chemical structure but only adjusts its physical structure to produce fiber products with better performance. One of the notable characteristics of regenerated cellulose fiber is its excellent moisture absorption and air permeability. This feature makes it stand out among all chemical fibers and is known as "breathing fabric". In addition to its excellent moisture absorption and air permeability, regenerated cellulose fiber also has many excellent properties such as softness, gloss, and smoothness. In the future, with the continuous advancement of science and technology and the continuous upgrading of consumer demand, regenerated cellulose fiber will surely play an important role in more fields and bring more beauty and comfort to human life.

[0003] However, the traditional regenerated cellulose fiber has poor mechanical properties under high humidity due to the breakage of hydrogen bonds between cellulose molecules in water, and is easy to break or deform and has low wet strength. At the same time, compared with synthetic fibers, the regenerated cellulose fiber has poor wear resistance and is easy to wear. In view of this, we propose a preparation method of mulberry bark regenerated cellulose fiber. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing mulberry bark regenerated cellulose fiber to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides a method for preparing mulberry bark regenerated cellulose fibers, which is used to prepare mulberry bark regenerated cellulose fibers with a fineness of 1.11 dtex-2.22 dtex and a length of 32-51 mm.

[0006] A method for preparing mulberry bark regenerated cellulose fiber comprises the following steps: S1.1, weigh the following raw materials in parts by weight: 1-5 parts by weight of composite modifier, 45-55 parts by weight of mulberry bark, 12-22 parts by weight of sodium hydroxide, 0.4-0.6 parts by weight of sodium hypochlorite, 5-7 parts by weight of carbon disulfide and 200-220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:0.5-1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 80-100 parts by weight of sulfuric acid, 150-250 parts by weight of sodium sulfate and 15-25 parts by weight of zinc sulfate; S1.2, the picked mulberry branches are destemmed, and then cut, cleaned and impurity-removed, and then steamed, rinsed, pulped, sanded, bleached, dried and solidified to obtain pulp; S1.3. The dried pulp is subjected to crushing, extrusion, yellowing, stirring, impurity removal, degassing, solidification spinning, stretching, cutting, washing and drying, oiling and drying to obtain mulberry bark regenerated cellulose fiber.

[0007] Preferably, the temperature in the digester in S1.2 is raised to 150-160°C at a heating rate of 1-5°C / min, kept warm for 5-8h, and beaten for 60-90min, with a beating concentration of 5-10%, a slurry concentration of 1-5%, and a pH value adjusted to 8-10; Preferably, the fiber in S1.3 is crushed and placed in an impregnation tank, and water is added and the fiber is immersed in a modified water-repellent agent after cutting, and reacted at 25-35°C for 30-50 minutes. After washing and drying, the fiber is immersed in a modified protective agent, and reacted at 60-80°C for 10-15 minutes.

[0008] Preferably, the steps for preparing the composite modifier are as follows: Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water, add buffer to adjust the pH value of the solution, dissolve sodium periodate in water, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react for 3-5 hours at 20-40° C., add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 1-3%, and obtain the modified water repellent; Preparation of modified protective agent: toluene diisocyanate and polyether polyol are mixed in a ratio of 1 to 3:1, heated to 50-60°C while stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1-2h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 50-60°C, the reaction time is 50-70min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained.

[0009] The main component of regenerated cellulose fiber is cellulose, which is a polysaccharide polymer composed of a large number of glucose units connected by β-1,4 glycosidic bonds. The cellulose molecule contains multiple hydroxyl functional groups. These hydroxyl groups can form hydrogen bonds, enhance the interaction force inside the fiber, and thus improve the mechanical strength of the fiber. However, when the fiber meets water, water molecules can insert between the cellulose molecular chains, destroying these hydrogen bonds, causing the interaction between cellulose molecules to weaken, thereby softening the fiber and reducing its strength in the wet state; the poor wear resistance is because the regenerated cellulose fiber undergoes a process of chemical dissolution and reprecipitation during the manufacturing process, which causes the fiber surface to be less smooth or strong than natural fibers. In addition, since the cellulose molecules undergo a certain degree of degradation during the chemical treatment process, resulting in a decrease in molecular weight, which affects the physical strength of the fiber, the regenerated cellulose fiber is more likely to break under friction, resulting in worse wear resistance than some synthetic fibers, such as polyester or nylon, which usually have higher molecular weights and more stable molecular structures.

[0010] Dialdehyde cellulose is a cellulose derivative containing aldehyde groups. It achieves cross-linking through the condensation reaction between the aldehyde groups and the hydroxyl groups in the cellulose molecules. The reaction mechanism involves the aldehyde-hydroxyl addition reaction between the aldehyde groups and the hydroxyl groups. The lone pair of electrons of the hydroxyl groups on the cellulose will attack the carbon atom of the aldehyde group in the dialdehyde cellulose molecule to form a tetrahedral intermediate. In the presence of an alkaline catalyst, the hydroxyl group in the semialdehyde compound will lose a water molecule to form a stable covalent bond, namely a methylene bridge. As the reaction proceeds, more dialdehyde cellulose molecules participate in the reaction and form more methylene bridges with the hydroxyl groups on the cellulose molecules, thereby constructing a three-dimensional cross-linked network structure. Under alkaline conditions, the hydroxyl groups on the cellulose molecules will be activated. ization, increasing its nucleophilicity. The activated cellulose hydroxyl group can react with the isocyanate group in the polyurethane prepolymer to form a carbamate bond. As the reaction proceeds, cross-linking points are formed between the cellulose molecules and the polyurethane, and a three-dimensional network structure is gradually constructed. Since the polyurethane has excellent elasticity, it can give the regenerated cellulose fiber higher elasticity and recovery ability, so that it can better restore its original shape after stretching, improve the durability and durability of the fiber, and enable it to maintain a good shape after repeated use or washing; at the same time, the unreacted aldehyde group and hydroxyl group on the dialdehyde cellulose can also react with the isocyanate group in the polyurethane molecule, which can firmly combine the polyurethane with the dialdehyde cellulose for further cross-linking.

[0011] The composite modifier is used to modify the regenerated cellulose fiber, and covalent bonds are formed through the cross-linking reaction of dialdehyde cellulose and regenerated cellulose fiber. Since these covalent bonds are more stable than hydrogen bonds and are not easily destroyed by water molecules, even in a humid environment, the regenerated cellulose fiber can still maintain a high interaction force, thereby improving the strength in a wet state. At the same time, the formation of cross-links can block moisture from entering the fiber and prevent water molecules from destroying the hydrogen bonds between cellulose molecules, thereby improving the wet strength of the fiber. In addition, the dimensional stability is better during washing and use, and the shrinkage rate is reduced, which can improve the dimensional stability. In addition, the three-dimensional network structure will also enhance the interaction force between cellulose molecules, thereby improving the wear resistance of the fiber. However, although the formation of cross-links can improve the wet strength, the formation of cross-links will also cause the fiber to become too rigid, thereby affecting its softness. Therefore, it is further combined with polyurethane to utilize the excellent properties of polyurethane. The elasticity and recovery of the polyurethane make up for the brittleness of cellulose itself, thereby improving the resilience and flexibility of the composite material. The flexible chain segments of the polyurethane can form a relatively tight entanglement with the cellulose molecules. The network structure effectively transmits stress and prevents relative sliding between molecules, so that the material is not easy to break when subjected to force, and can better recover to its original state, thereby improving the flexibility and tear resistance of the material. Therefore, dialdehyde cellulose improves the mechanical properties of the fiber through cross-linking, while polyurethane provides additional elasticity, wear resistance and protective layer. When the two are used in combination, not only can the strength and stability of the fiber be enhanced, but also the resilience of the fiber can be improved, making it easier for the fiber to recover to its original state after stretching. At the same time, dialdehyde cellulose and polyurethane can also interact with each other to improve the binding force on the regenerated cellulose fiber. The three are tightly combined, the structure is stable, and it is not easy to fall off from the regenerated cellulose fiber, maintaining its performance while improving durability.

[0012] Preferably, the concentration of the microcrystalline cellulose is 1-5% (w / v).

[0013] Preferably, the molar concentration of the sodium periodate is 0.1-0.5 mol / L, and the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 0.5-2.

[0014] Preferably, the polyether polyol is prepared by base-catalyzed polymerization of ethylene oxide.

[0015] Preferably, the buffer solution is sodium acetate and acetate buffer solution, and the pH value of the solution is adjusted to 5-7.

[0016] Preferably, the amount of the sodium sulfite reducing agent added is 1.5-2 times the molar amount of sodium periodate.

[0017] Compared with the prior art, the present invention has the following beneficial effects: In the preparation method of mulberry bark regenerated cellulose fiber, a composite modifier is used to prepare a mulberry bark regenerated cellulose fiber, dialdehyde cellulose is used to cross-link with the regenerated cellulose fiber to prevent moisture from penetrating into the fiber, and the hydrogen bonds between cellulose molecules are protected from being destroyed, thereby improving the wet strength, and the excellent elasticity and toughness of polyurethane are covalently bonded with cellulose to form a protective layer, thereby improving the elasticity and wear resistance of the fiber, and the synergistic effect of the three is used to promote the improvement of the wet strength, elasticity, dimensional stability, wear resistance and shrinkage rate of the regenerated cellulose fiber. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] Embodiment 1: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 3 parts by weight of composite modifier, 55 parts by weight of mulberry bark, 22 parts by weight of sodium hydroxide, 0.6 parts by weight of sodium hypochlorite, 7 parts by weight of carbon disulfide and 220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:0.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 100 parts by weight of sulfuric acid, 250 parts by weight of sodium sulfate and 25 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 2; the amount of sodium sulfite reducing agent added is twice the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0020] Embodiment 2: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 3 parts by weight of composite modifier, 55 parts by weight of mulberry bark, 22 parts by weight of sodium hydroxide, 0.6 parts by weight of sodium hypochlorite, 7 parts by weight of carbon disulfide and 220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:1; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 100 parts by weight of sulfuric acid, 250 parts by weight of sodium sulfate and 25 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 2; the amount of sodium sulfite reducing agent added is twice the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0021] Embodiment 3: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 3 parts by weight of composite modifier, 55 parts by weight of mulberry bark, 22 parts by weight of sodium hydroxide, 0.6 parts by weight of sodium hypochlorite, 7 parts by weight of carbon disulfide and 220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 100 parts by weight of sulfuric acid, 250 parts by weight of sodium sulfate and 25 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 2; the amount of sodium sulfite reducing agent added is twice the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0022] Embodiment 4: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 3 parts by weight of composite modifier, 45 parts by weight of mulberry bark, 12 parts by weight of sodium hydroxide, 0.4 parts by weight of sodium hypochlorite, 5 parts by weight of carbon disulfide and 200 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 80 parts by weight of sulfuric acid, 150 parts by weight of sodium sulfate and 15 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 0.5; the amount of sodium sulfite reducing agent added is 1.5 times the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0023] Embodiment 5: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 1 part by weight of composite modifier, 55 parts by weight of mulberry bark, 22 parts by weight of sodium hydroxide, 0.6 parts by weight of sodium hypochlorite, 7 parts by weight of carbon disulfide and 220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 100 parts by weight of sulfuric acid, 250 parts by weight of sodium sulfate and 25 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 2; the amount of sodium sulfite reducing agent added is twice the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0024] Embodiment 6: A method for preparing mulberry bark regenerated cellulose fiber, comprising the following steps: S1.1, weigh the following raw materials in parts by weight: 5 parts by weight of composite modifier, 55 parts by weight of mulberry bark, 22 parts by weight of sodium hydroxide, 0.6 parts by weight of sodium hypochlorite, 7 parts by weight of carbon disulfide and 220 parts by weight of coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 100 parts by weight of sulfuric acid, 250 parts by weight of sodium sulfate and 25 parts by weight of zinc sulfate; the molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 2; the amount of sodium sulfite reducing agent added is twice the molar amount of sodium periodate; the polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide; Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water to prepare a solution with a concentration of 5% (w / v), add sodium acetate and acetate buffer to adjust the pH value of the solution to 5, dissolve sodium periodate in water with a molar concentration of 0.5 mol / L, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react at 40°C for 3h, add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 3%, and obtain the modified water repellent; Preparation of modified protective agent: Toluene diisocyanate and polyether polyol are mixed in a ratio of 2:1, heated to 60°C under stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 60°C, the reaction time is 50min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained; S1.2. Remove the stems of the picked mulberry branches, and then cut, clean and remove impurities to obtain the raw mulberry bark. Add the raw mulberry bark and sodium hydroxide solution into a cooker. The relative amount of sodium hydroxide is 15% and the liquid ratio is 1:3. The temperature is raised to 150℃ at a heating rate of 5℃ / min and kept warm for 5h. After the cooking is completed, the residual liquid is discharged and the cooked mulberry bark is rinsed to achieve a dynamic viscosity of 30mpa.s and a cellulose content of ≥90% of the cooking quality. The mulberry bark after cooking is then beaten with a pulping machine for 90 minutes with a sticky pulping concentration of 5%, until there are no small pulp clumps in the pulp, the obtained pulp is desanded in a desander, and then chlorinated and bleached with sodium hypochlorite, wherein the effective chlorine amount is 6% relative to the absolute dry material amount, the pulp concentration is 5%, the pH value is adjusted to 10, the reaction is carried out at 40°C for 60 minutes, the residual liquid is removed and rinsed, the pulp is pulped in a pulping machine, and the pulp is naturally dried and solidified to obtain pulp; S1.3. Use a crusher to further crush the dried pulp, put it into an impregnation tank, add water and soak it at 40°C for 30 minutes, squeeze the impregnated pulp through a press to remove excess impregnation liquid, place it in a well-ventilated environment for natural aging, then add carbon disulfide and a 40% by mass sodium hydroxide solution to the cellulose in a sealed container to mix and yellow, add a 10% by mass sodium hydroxide solution to the yellowed cellulose xanthate, stir to promote the dissolution of the cellulose xanthate to form a viscose solution, use a filter to remove impurities in the viscose solution, The bubbles in the viscose solution are removed by vacuum degassing, the degassed viscose solution is extruded through a spinneret, and enters a coagulation bath to solidify and spin at 30°C to form fibers, the fibers are stretched by a mechanical device, and cut by a cutting device, and then the fibers are immersed in a modified water-repellent agent, reacted at 35°C for 30 minutes, washed and dried, immersed in a modified protective agent, reacted at 80°C for 10 minutes, and finally the fibers are washed, oiled and dried to obtain mulberry regenerated cellulose fibers, the fineness of the obtained mulberry regenerated cellulose fibers is 1.33 dtex, and the length is 38 mm.

[0025] Comparative Example 1: The method of Example 3 was adopted without using a composite modifier to prepare mulberry bark regenerated cellulose fiber.

[0026] Comparative Example 2: The method of Example 3 was adopted, and the addition amount of the composite modifier was 10 parts by weight.

[0027] Comparative Example 3: The method of Example 3 was adopted, only the modified water-repellent agent was added to prepare the mulberry bark regenerated cellulose fiber, and no modified protective agent was added.

[0028] Comparative Example 4: The method of Example 3 was adopted, only the modified protective agent was added to prepare the mulberry bark regenerated cellulose fiber, and no modified water repellent was added.

[0029] The present invention discloses a method for preparing a mulberry bark regenerated cellulose fiber by using a composite modifier, wherein the performance index inspection items and inspection standards of the method for preparing the mulberry bark regenerated cellulose fiber are as follows: Refer to GB-T 14337-2008 Test Method for Tensile Properties of Chemical Staple Fibers. The wet strength test evaluates the mechanical properties of the fiber in a wet state by measuring the breaking strength and breaking elongation of the fiber in a wet state. The specific test steps require the sample to be immersed in water for 24 hours to simulate the use conditions under high humidity. The compression elastic recovery rate refers to the ability of the fiber to recover its initial thickness or volume after being compressed. It can be used to measure the elastic properties of the fiber. Weigh (5±0.1)g of loose fiber sample, gently make 5 cotton nets with an area of ​​about 10cm×10cm by hand, and then gently put them into the bulking characteristic instrument. After standing for 5 minutes, slowly put down the pressure block A (light load 60g), read the height h1 of the sample after 1 minute, slowly put down the pressure block B (heavy load at this time is 560g) on ​​the basis of light load, read the height h2 after 1 minute, remove the heavy load, stand for 3 minutes, and then slowly put down the light load, read the height h3 after 1 minute, the compression elastic recovery rate E (%) = (h3-h2) / (h1-h2).

[0030] According to the above standards, the preparation method of a mulberry bark regenerated cellulose fiber prepared in the above Examples 1-6 and Comparative Examples 1-4 was tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-4 The above data fully show that compared with Comparative Examples 1-4, Examples 1-6 can fully show the effect of the composite modifier on the wet strength and elasticity of a preparation method of mulberry bark regenerated cellulose fiber.

[0031] Since the present invention adopts a composite modifier to prepare a method for preparing mulberry peel regenerated cellulose fiber, the composite modifier effectively improves the wet strength and elasticity of the mulberry peel regenerated cellulose fiber, as follows: It can be seen from Examples 1-3 that as the proportion of components in the composite modifier continues to change, the wet strength and elasticity of the mulberry regenerated cellulose fiber continue to change. This is because dialdehyde cellulose forms a network structure by covalently cross-linking with the regenerated cellulose fiber, thereby improving the wet strength and dimensional stability of the fiber. The good flexibility of the polyurethane prepolymer can form physical entanglements inside the fiber, which helps to enhance the toughness of the fiber. As the polyurethane component continues to increase, the fiber flexibility is improved, and the interaction between the polyurethane and dialdehyde cellulose is also enhanced. The three are closely combined, thereby improving the wet strength.

[0032] It can be seen from Examples 3 and 4 that with the continuous increase in the content of other components for preparing the mulberry regenerated cellulose fiber, the wet strength and elasticity of the mulberry regenerated cellulose fiber have almost no obvious change. This is because the composite modifier is the main factor affecting the wet strength and elastic properties of the mulberry regenerated cellulose fiber, and the other components play an auxiliary role in the wet strength and elastic properties of the mulberry regenerated cellulose fiber. When the content of the composite modifier is constant, changes in the other components within a certain range will not cause significant changes in the wet strength and elastic properties of the mulberry regenerated cellulose fiber.

[0033] It can be seen from Examples 5 and 6 that with the continuous change of the content of the composite modifier, the wet strength and elasticity of the mulberry regenerated cellulose fiber continue to change. This is because the dialdehyde cellulose can cross-link with the regenerated cellulose fiber to form a network structure, and the chemical bond is more stable than the hydrogen bond, thereby improving the wet strength of the regenerated cellulose fiber. The polyurethane prepolymer can form a protective layer on the surface of the regenerated cellulose fiber to improve the wear resistance and elastic properties of the fiber. However, when the content of the composite modifier gradually increases, the degree of cross-linking increases, which makes the fiber hard and brittle. Therefore, with the increase of the content of the composite modifier, the wet strength and elasticity of the mulberry regenerated cellulose fiber first increase and then decrease.

[0034] According to the above test experiments, the method for preparing a mulberry bark regenerated cellulose fiber prepared according to Example 3 has the best performance, so Example 3 is taken as the best example; By comparing Example 3 with Comparative Examples 1-4, it can be seen that: In Comparative Example 1, mulberry bark regenerated cellulose fibers were prepared without using a composite modifier. The wet strength and elasticity of the mulberry bark regenerated cellulose fibers were poor. This is because the main component of the regenerated cellulose fibers is still cellulose. In a dry state, the molecules of the regenerated cellulose fibers are mainly connected to each other by hydrogen bonds to form a stable structure. However, in a humid environment, water molecules can be inserted into the hydrogen bonds between the molecules of the regenerated cellulose fibers, weakening the force of these hydrogen bonds, thereby causing the wet strength of the regenerated cellulose fibers to decrease. Without using a composite modifier, the regenerated cellulose fibers lack additional cross-linking structures and are more susceptible to the influence of water molecules, causing the structure of the regenerated cellulose fibers to become unstable, thereby affecting their strength.

[0035] In Comparative Example 2, the addition amount of the composite modifier is 10 parts by weight, and the wet strength and elasticity of the mulberry regenerated cellulose fiber are poor. This is because excessive addition of the composite modifier will lead to excessive crosslinking and too many crosslinking points between cellulose molecules, making the fiber too rigid, thereby reducing its elasticity and softness. At the same time, excessive polyurethane will cause the fiber surface to be too sticky or form an inappropriate surface layer, which will affect the mechanical properties of the fiber. As a result, the wet strength and elasticity of the mulberry regenerated cellulose fiber deteriorate.

[0036] In Comparative Example 3, only a modified water-repellent agent was added to prepare mulberry regenerated cellulose fiber, and no modified protective agent was added. The wet strength and elasticity of the mulberry regenerated cellulose fiber were poor. This is because dialdehyde cellulose is mainly used to form covalent bonds between cellulose molecules through a cross-linking reaction, thereby improving the wet strength and dimensional stability of the fiber. However, relying solely on the cross-linking reaction, although it can improve the wet strength of the fiber to a certain extent, will cause the fiber to become too rigid and lack the necessary elasticity and softness.

[0037] In Comparative Example 4, only a modified protective agent was added to prepare mulberry regenerated cellulose fiber, and no modified water-repellent agent was added. The wet strength and elasticity of the mulberry regenerated cellulose fiber were poor. This is because polyurethane mainly provides elasticity, softness and resilience. Although it can improve the flexibility and resilience of the fiber, polyurethane alone cannot effectively improve the strength of the fiber under wet conditions, causing the fiber to lose its original interaction force under wet conditions, thereby weakening the wet strength.

[0038] In summary, the modification is prepared by using a composite modifier, and dialdehyde cellulose is used to cross-link with regenerated cellulose fibers to prevent moisture from penetrating into the fibers. The hydrogen bonds between cellulose molecules are protected from being destroyed, thereby improving the wet strength. The excellent elasticity and toughness of polyurethane are covalently bonded with cellulose to form a protective layer, thereby improving the elasticity and wear resistance of the fibers. The synergistic effect of the three is used to improve the wet strength, dimensional stability and shrinkage performance of the regenerated cellulose fibers.

[0039] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing mulberry bark regenerated cellulose fiber, characterized in that: Used to prepare mulberry skin regenerated cellulose fiber with a fineness of 1.11dtex-2.22dtex and a length of 32-51mm; The method comprises the following steps: S1.1, weighing the following raw materials in parts by weight: 1-5 parts by weight of a composite modifier, 45-55 parts by weight of mulberry bark, 12-22 parts by weight of sodium hydroxide, 0.4-0.6 parts by weight of sodium hypochlorite, 5-7 parts by weight of carbon disulfide and 200-220 parts by weight of a coagulation bath; The composite modifier is composed of a modified water-repellent agent and a modified protective agent in a mass ratio of 1:0.5-1.5; The modified water-repellent agent is dialdehyde cellulose prepared from microcrystalline cellulose and sodium periodate, and the modified protective agent is a polyurethane prepolymer prepared from toluene diisocyanate and polyether polyol. The coagulation bath is composed of 80-100 parts by weight of sulfuric acid, 150-250 parts by weight of sodium sulfate and 15-25 parts by weight of zinc sulfate; S1.2, the picked mulberry branches are destemmed, and then cut, cleaned and impurity-removed, and then steamed, rinsed, pulped, sanded, bleached, dried and solidified to obtain pulp; S1.

3. The dried pulp is subjected to crushing, extrusion, yellowing, stirring, impurity removal, degassing, solidification spinning, stretching, cutting, washing and drying, oiling and drying to obtain mulberry bark regenerated cellulose fiber.

2. The method for preparing mulberry bark regenerated cellulose fiber according to claim 1, characterized in that: In the S1.2, the temperature in the digester is raised to 150-160°C at a heating rate of 1-5°C / min, kept warm for 5-8h, and pulped for 60-90min, with a pulping concentration of 5-10%, a slurry concentration of 1-5%, and the pH value is adjusted to 8-10.

3. The method for preparing mulberry bark regenerated cellulose fiber according to claim 1, characterized in that: After being crushed in S1.3, the fiber is put into an impregnation tank, and water is added to impregnate for 30-50 minutes at 30-40°C. After being cut, the fiber is immersed in a modified water-repellent agent, and reacted at 25-35°C for 30-50 minutes. After being washed and dried, the fiber is immersed in a modified protective agent, and reacted at 60-80°C for 10-15 minutes.

4. The method for preparing mulberry bark regenerated cellulose fiber according to claim 1, characterized in that: The steps of preparing the composite modifier are specifically as follows: Preparation of modified water repellent: firstly, disperse microcrystalline cellulose powder in water, add buffer to adjust the pH value of the solution, dissolve sodium periodate in water, and add it to the dispersed microcrystalline cellulose solution, stir continuously with a stirrer, react for 3-5 hours at 20-40° C., add sodium sulfite reducing agent to terminate the reaction, remove unreacted oxidant and other by-products by filtering and washing, and finally dry the product to constant weight to obtain dialdehyde cellulose, prepare the dialdehyde cellulose into a solution with a mass fraction of 1-3%, and obtain the modified water repellent; Preparation of modified protective agent: toluene diisocyanate and polyether polyol are mixed in a ratio of 1 to 3:1, heated to 50-60°C while stirring, dibutyltin dilaurate catalyst is added, the reaction time is 1-2h, 1,4-butanediol chain extender is added to the above solution, stirring is continued and the temperature is maintained at 50-60°C, the reaction time is 50-70min, and a polyurethane prepolymer, i.e., a modified protective agent, is obtained.

5. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The concentration of the microcrystalline cellulose is 1-5% (w / v).

6. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The molar concentration of the sodium periodate is 0.1-0.5 mol / L.

7. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The polyether polyol is prepared by alkali-catalyzed polymerization of ethylene oxide.

8. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The buffer solution is sodium acetate and acetic acid buffer solution, and the pH value of the solution is adjusted to 5-7.

9. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The amount of the sodium sulfite reducing agent added is 1.5-2 times the molar amount of sodium periodate.

10. The method for preparing mulberry bark regenerated cellulose fiber according to claim 4, characterized in that: The molar ratio of the amount of sodium periodate added to the cellulose repeating unit is 0.5-2.

Citation Information

Patent Citations

  • Mulberry cell fiber and preparation method thereof

    CN103255483A

  • Preparation method of toughened antimicrobial mulberry fiber

    CN108103605A

  • Method for preparing fine denier strong viscose fibers

    CN108677273A

  • Biomass modified regenerated cellulose fiber based on sugar modification and preparation method thereof

    CN114892295A

  • Mildew-proof breathable fabric and preparation method thereof

    CN115354504A